Outcomes of the PIRASOA programme, an antimicrobial stewardship programme implemented in hospitals of the Public Health System of Andalusia, Spain: an ecologic study of time-trend analysis. (March 2020) - Rodríguez-Baño, J.; Pérez-Moreno, M.A.; Peñalva, G.; Garnacho-Montero, J.; Pinto, C.; Salcedo, I.; Fernández-Urrusuno, R.; Neth, O.; Gil-Navarro, M.V.; Pérez-Milena, A.; Sierra, R.; Estella, Á.; et al.
Abstract: Objectives: Inappropriate antimicrobial use favours the spread of resistance, and multidrug-resistant microorganisms (MDR) are currently of major concern. Antimicrobial stewardship programmes (ASPs) are essential for improving antibiotic use in hospitals. However, their impact on entire healthcare systems has not been thoroughly assessed. Our objective was to provide the results of an institutionally supported ASP involving 31 public hospitals in Andalusia, Spain. Methods: We designed an ecologic time-series study from 1 January 2014 to 31 December 2017. Quarterly, data on indicators were collected prospectively, and feedback reports were provided. PIRASOA is an ongoing clinically based quality-improvement programme whose key intervention is the educational interview, regular peer-to-peer interventions between advisors and prescribers to reinforce the appropriate use of antibiotics. Seventy-two indicators were monitored to measure prescribing quality (inappropriate treatments), antimicrobial consumption (defined daily doses per 1000 occupied bed-days), incidence density of MDR per 1000 occupied bed-days and crude mortality rate associated with bloodstream infections. We used Joinpoint regression software to analyse the trends. Results: The quality of antimicrobial prescribing improved markedly, and the inappropriate treatment rate was significantly lower, with quarterly percentage change (QPC) = −3.0%, p < 0.001. Total antimicrobial consumption decreased (QPC = −0.9%, p < 0.001), specifically carbapenems, amoxicillin/clavulanic acid, quinolones and antifungal agents, whereas antipseudomonal cephalosporin use increased. While the incidence of MDR showed a sustained decreasing trend (QPC = −1.8%; p 0.002), the mortality of patients with bloodstream infections remained stable (QPC = −0.2%, p 0.605). Conclusions: To date, the PIRASOA programme has succeeded in optimizing the use of antimicrobial agents and has had a positive ecologic result on bacterial resistance at level of an entire healthcare system.